1981
DOI: 10.1126/science.7209531
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Lines of Basophil/Mast Cells Derived from Normal Mouse Bone Marrow

Abstract: Nonadherent tissue culture cell lines were established from normal bone marrow of a variety of mouse strains. The lines possessed morphological and histochemical markers of the basophil/mast cell and contained committed stem cells for metachromatic cells. Their derivation from normal marrow and their lack of tumorigenicity despite long-term culture makes these cell lines potentially important for studies of the mechanisms of allergic reactions and inflammation as well as the differentiation pathways involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…Therefore, some morphologically identifiable mast cells in the peritoneal cavity may function as the mast cell precursors. Since peritoneal mast cells appear to float in the fluid, the proliferative potentiality of some peritoneal mast cells reminds us of the suspension culture system of mast cell-like cells that has been devised in many laboratories (41)(42)(43)(44)(45)(46). However, mitosis of peritoneal mast cells is seldom observed in intact animals (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some morphologically identifiable mast cells in the peritoneal cavity may function as the mast cell precursors. Since peritoneal mast cells appear to float in the fluid, the proliferative potentiality of some peritoneal mast cells reminds us of the suspension culture system of mast cell-like cells that has been devised in many laboratories (41)(42)(43)(44)(45)(46). However, mitosis of peritoneal mast cells is seldom observed in intact animals (10).…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells are believed to be the major source of IL-3, although WEHI-3, classified as a myelomonocytic leukemic cell line, produces it constitutively. In the short time since WEHI-3 was shown to produce IL-3, it has been found that the factor also has the ability to stimulate the growth in vitro of many kinds of hemopoietic cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and it has been called by some a multispecific colony-stimulating factor (20).…”
Section: Introductionmentioning
confidence: 99%
“…Activated T cells are believed to be the major source of IL-3, although WEHI-3, classified as a myelomonocytic leukemic cell line, produces it constitutively. In the short time since WEHI-3 was shown to produce IL-3, it has been found that the factor also has the ability to stimulate the growth in vitro of many kinds of hemopoietic cells (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and it has been called by some a multispecific colony-stimulating factor (20).It has been shown to be identical with Schrader's P-cellstimulating factor (21) and with stem cell-activating factor (22).It has been recognized for some time that early erythroid progenitors require a second factor, burst-promoting activity (BPA), in addition to the hormone erythropoietin (Ep) for their full development in culture (23-26). The ability of IL-3 to stimulate erythropoiesis has been attributed to its activity as a burst promoter in the production of differentiated erythrocytes in vitro from the burst-forming progenitor or erythroid burst-forming units (BFU-E) (17, 27).…”
mentioning
confidence: 99%
“…Primary cell lines were obtained by mincing tissues and culturing them in Dulbecco modified Eagle medium (GIBCO Laboratories, Grand Island, N.Y.) supplemented with 10% fetal calf serum (GIBCO) at 37°C in 5% C02-95% air. Spleen cells were cultured in RPMI 1640 medium supplemented with 10% fetal calf serum, antibiotics, and 10% WEHI-3-conditioned medium (19,32). Serum-free medium was used as described previously (30), except that the only supplements were insulin and transferrin.…”
mentioning
confidence: 99%